2022
DOI: 10.1093/jjco/hyac002
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the coronavirus disease 2019 pandemic on first-visit patients with oesophageal cancer in the first infection wave in Saitama prefecture near Tokyo: a single-centre retrospective study

Abstract: Background Although the novel coronavirus disease 2019 did not lead to a serious medical collapse in Japan, its impact on treatment of oesophageal cancer has rarely been investigated. This study aimed to investigate the influence of the pandemic on consultation status and initial treatment in patients with primary oesophageal cancer. Methods A retrospective study was conducted among 546 patients with oesophageal cancer who vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…The number of patients with gastric cancer may increase due to an increase in the number of screening or follow-up endoscopies from September to December, when the number of COVID-19 patients was relatively low, as a result of patients refraining from screening endoscopy before that period. Additionally, the number of esophageal cancer patients at our hospital also showed a similar trend during the same period [ 13 ].…”
Section: Discussionmentioning
confidence: 78%
“…The number of patients with gastric cancer may increase due to an increase in the number of screening or follow-up endoscopies from September to December, when the number of COVID-19 patients was relatively low, as a result of patients refraining from screening endoscopy before that period. Additionally, the number of esophageal cancer patients at our hospital also showed a similar trend during the same period [ 13 ].…”
Section: Discussionmentioning
confidence: 78%
“…In their retrospective study consisting of 556 patients at a single center in Japan from 2018–2021, Miyawaki et al reported a significant decrease in the number of newly diagnosed EC cases during the first wave of the pandemic. Additionally, they noted an increased proportion of patients diagnosed with distant metastases ( 19 ). Another Japanese study reported 1.9% and 3.1% decreases in overall new cancer diagnoses and new EC diagnoses during the pandemic as compared to the average rates from 2016–2019.…”
Section: Resultsmentioning
confidence: 99%
“…In this systematic review investigating the impact of resource allocation during the COVID-19 pandemic on patients with EC, several points were noteworthy. For one, reductions in rates of new EC diagnoses were essentially ubiquitous, with up to a 26% reduction noted in some studies ( 6 , 7 , 19 , 20 , 24 , 25 , 28 ). Decreased EC diagnosis was accompanied by inconsistent results regarding the disease severity at presentation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Emission factors are defined by the quantity of fuel burned while generating energy. Over the years, Japan has increased its use of renewable energy sources for electricity production and resumed nuclear power plant operations [37]. Notably, in the NUH campus, the carbon footprints of factors other than pharmaceuticals and medical supplies have reduced over the years.…”
Section: Discussionmentioning
confidence: 99%